Assessment of platelet activation in myeloproliferative disorders with complementary techniques - Bermejo, Emilse (2004)
Bleeding and thrombosis in myeloproliferative disorders (MPD) are common events, sometimes both are present in the same patient during the course of the disease. Platelet activation in patients with MPD is often suggested. The present study analyses the presence of circulating activated platelets, using simultaneously flow cytometry and aggregometric studies in MPD. We studied 28 patients: 13 with polycythaemia vera, seven with essential thrombocythaemia, and eight chronic myeloid leukaemia. We performed functional tests, aggregation and adenosine triphosphate (ATP) release and flow cytometric assays (mepacrine staining and platelet activation markers CD62, CD63 and fibrinogen binding (B-FG)). Twenty-one MPD samples (75%) had reduced aggregation and ATP release. Acquired δ-SPD was detected in 11 of 28 MPD patients (39%), and we found no association between reduced mepacrine labelling and abnormal ATP release. High levels of activation markers were obtained: CD62 in 19 of 28 patients (68%), CD63 in 13 of 28 patients (46%) and B-FG in 19 of 28 patients (68%). The most prevalent abnormality was a reduced aggregation and ATP release. The lack of association between ATP release and mepacrine labelling suggests that other mechanisms, besides the deficit of intraplatelet ATP/adenosine diphosphate, might occur. High levels of activation markers were also observed. We conclude that both tests are complementary and necessary to understand the functional status of platelets in MPD.